2020
DOI: 10.1088/1757-899x/861/1/012056
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bi addition on Si features, tensile properties and wear resistance of hypereutectic Al-15Si alloy

Abstract: Al-Si alloys are very important in the automotive industry. This is thanks to their high strength to weight ratio, suitable fluidity, good corrosion resistance and high productivity. The shape of the eutectic Silicon (Si) has been widely studied since it is considered an index of quality regarding many application properties. Understanding the effects of alloy additions on the morphology of Si has drawn researcher’s attention. One of these elements of interest is Bismuth (Bi), which may be part of the composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…[7][8][9] Bismuth is also used as a chemical refiner for the eutectic silicon flakes in both hypoeutectic and hypereutectic Al-Si alloys resulting in higher tensile and wear resistance performances. [10][11][12][13][14][15] It is known how Bi can counteract, even as a trace element, the effect of further alloying additions or preliminary molten metal treatments affecting the final microstructure and tensile performance of the alloy. Some studies [16,17] stated how the presence of Bi in Sr-modified Al-Si foundry alloys increases the eutectic growth temperature, and a fibrous to the plate-like transition of eutectic Si occurs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] Bismuth is also used as a chemical refiner for the eutectic silicon flakes in both hypoeutectic and hypereutectic Al-Si alloys resulting in higher tensile and wear resistance performances. [10][11][12][13][14][15] It is known how Bi can counteract, even as a trace element, the effect of further alloying additions or preliminary molten metal treatments affecting the final microstructure and tensile performance of the alloy. Some studies [16,17] stated how the presence of Bi in Sr-modified Al-Si foundry alloys increases the eutectic growth temperature, and a fibrous to the plate-like transition of eutectic Si occurs.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7–9 ] Bismuth is also used as a chemical refiner for the eutectic silicon flakes in both hypoeutectic and hypereutectic Al–Si alloys resulting in higher tensile and wear resistance performances. [ 10–15 ]…”
Section: Introductionmentioning
confidence: 99%
“…Pereira et al [26] recently demonstrated that the tensile properties of the Al-15 wt.% Si-1 wt.% Bi alloy are higher than those of the non-modified Al-15 wt.% Si alloy. It is demonstrated that the addition of Bi to hypereutectic Al-Si alloys facilitates improvement in alloy strength.…”
Section: Introductionmentioning
confidence: 99%